From Slavery to Freedom : A History of Negro Americans - Franklin, John Hope (New York Alfred A. Knopf, 1967)
From Slavery to Freedom remains the most revered, respected, and honored text on the market. The preeminent history of African Americans, this best-selling text charts the journey of African Americans from their origins in Africa, through slavery in the Western Hemisphere, struggles for freedom in the West Indies, Latin America, and the United States, various migrations, and the continuing quest for racial equality. Building on John Hope Franklin's classic work, the ninth edition has been thoroughly rewritten by the award-winning scholar Evelyn Brooks Higginbotham. It includes new chapters and updated information based on the most current scholarship. With a new narrative that brings intellectual depth and fresh insight to a rich array of topics, the text features greater coverage of ancestral Africa, African American women, differing expressions of protest, local community activism, black internationalism, civil rights and black power, as well as the election of our first African American president in 2008. The text also has a fresh new 4-color design with new charts, maps, photographs, paintings, and illustrations.
Include Illustrations, Bibliography and Index.
Keywords: African Americans -- Slavery -- United States -- Blacks -- United States